2023
DOI: 10.3390/jcm12175486
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Ischemia-Modified Albumin as a Biomarker for Acute Appendicitis: A Systematic Review and Meta-Analysis

Apoorv Singh,
Zenon Pogorelić,
Aniket Agrawal
et al.

Abstract: Background: Acute appendicitis is a frequently encountered surgical emergency. Despite several scoring systems, the possibility of delayed diagnosis persists. In addition, a delayed diagnosis leads to an increased risk of complicated appendicitis. Hence, there is a need to identify biological markers to help clinicians rapidly and accurately diagnose and prognosticate acute appendicitis with a high sensitivity and specificity. Although several markers have been evaluated, the pressing concern is still the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Several studies have suggested that the measurement of structurally modified albumin could assist with monitoring oxidative stress in several clinical conditions, such as renal failure, ischemic heart disease, acute appendicitis, cerebral infarction, and pre-eclampsia [ 19 , 20 , 21 , 22 , 23 ]. It is well known that IPF patients exhibit heightened systemic and tissue oxidative stress levels, influenced by various contributing factors that exacerbate this oxidative burden within the disease context [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that the measurement of structurally modified albumin could assist with monitoring oxidative stress in several clinical conditions, such as renal failure, ischemic heart disease, acute appendicitis, cerebral infarction, and pre-eclampsia [ 19 , 20 , 21 , 22 , 23 ]. It is well known that IPF patients exhibit heightened systemic and tissue oxidative stress levels, influenced by various contributing factors that exacerbate this oxidative burden within the disease context [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research expanded this finding, revealing that serum IMA concentrations increased in various pathological conditions linked to oxidative stress. As a result, it has been regarded not only as a biomarker of ischemia but also as an indicator of oxidative stress within diverse pathological contexts [ 19 , 20 , 21 , 22 , 23 ]. This study aims to explore the possible association between the serum concentrations of IMA and adverse clinical outcomes in patients diagnosed with IPF and, therefore, provide initial mechanistic insights into the factors mediating the link between oxidative stress and disease progression in this group.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with dialysis were included, the subgroup analyses by renal function were performed. The success of the eradication was assessed via a 13 C-urea breath test 6 weeks after the eradication. CCr was monitored for 3 months before the start of the study and during the study to ensure that it remained constant.…”
Section: Background and Methods In Included Studiesmentioning
confidence: 99%
“…Regarding non-randomized controlled trials, the quality of the research was evaluated based on the Newcastle-Ottawa Scale [12,13]. The Newcastle-Ottawa Scale consists of 4 items for selection, 2 items for comparability, and 3 items for outcome or exposure.…”
Section: Quality Assessment Of Included Papersmentioning
confidence: 99%
“…These markers offer insights into the neonate’s inflammatory status and immune response, which are intricately linked to the development of neurological complications [ 13 , 14 ]. Similarly, these markers proved to be valuable resources in studying other different conditions such as tumor pathology or inflammatory conditions [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%